Study of Cardiovascular Risks in Adolescents (ERICA): alcohol consumption and associated factors - Fernanda Garcia Gabira Miguez; Gabriela Oliveira; Marcia Mara Correa; Elizabete Regina Araújo Oliveira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze factors that influence alcohol consumption by Brazilian adolescents aged 12 to 17 years from the five macro-regions of Brazil, according to sociodemographic, schooling, and family characteristics. Methods: This is a cross-sectional study with data from the Study of Cardiovascular Risks in Adolescents (ERICA). The outcome was assessed by alcohol consumption and considered the variables sex, age, ethnicity/skin color, maternal schooling level, having housemaids, number of bathrooms at home, living or not with parents, and type of school. For the analyses, the survey mode was used for complex samples. Poisson regression was performed to assess the magnitude of factors associated with alcohol consumption among adolescents. Results: The prevalence of alcohol consumption by adolescents was 22.1%. The variables age range of 15 to 17 years, higher socioeconomic status, and living alone or with only one of the parents were factors that remained associated with alcohol consumption by adolescents regardless of their region of residence. Protective factors in alcohol consumption were associated with variables related to lower economic conditions and being of Asian or indigenous descent. Conclusion: The percentage of adolescents who consume alcohol is worrisome and must be tackled with public policies and health education. Understanding which factors are related to this situation contributes to practices and policies aimed to reduce its prevalence and damage to health.